The colour and luminiscence of Tugtupite (Beryllosodalite) from Ilímaussaq, South Greenland. - Povarennykh, A. S.; Platonov, A. M.; Tarashchan, A. N.; Belichenko, V. P. (Meddelelser om Grønland, 1971)
Tugtupite, Na4[BeAlSi4O12] Cl, is a mineral with bright pink colour and yellow-orange UV-luminescence. The visible region of the spectral absorption curves and the luminescence spectrum of tugtupite from the Ilímaussaq alkaline massif (South Greenland) were studied. Calculated and experimental values of vibrational frequencies of different molecular ions were compared, and it was established that the luminescence of tugtupite is caused by S2- molecular ions occupying the position of Cl ions in the crystal structure. These ions are also the cause of the colour of tugtupite, probably in combination with other, thermically less stable, radiation centres.